Perfil clínico e epidemiológico dos pacientes transplantados de órgãos sólidos com infecção de corrente sanguínea por bactérias gram negativas e gram positivas - Camargo, Thiago Zinsly Sampaio [UNIFESP] (2011)
Objectives: To describe clinical and epidemiological differences, beyond clinical risk factors for death in solid organ transplant patients with Bloodstream Infections (BSI) caused by Gram Negative (GN) and Gram Positive (GP) bacteria. Methods: We performed a retrospective analysis of medical records, which were evaluated patients undergoing solid organ transplantation with BSI in the period from January 2000 to January 31, 2006 in the São Paulo and the Kidney and Hypertension Hospitals, São Paulo, Brazil. It was also performed the analysis of risk factors for death. Results: 195 patients were included in this study with a mean age of 43.3 (+ 0.90) years and 114 (58.5%) were male. 168 (86.2%) were kidney transplants, 16 (8.2%) kidney-pancreas, 5 (2.6%) heart, 5 (2.6%) liver and 1 (0.5%) liverkidney. The mean hospital stay was 34.2 (+ 62.7) days. Were caused by GN 147 (75.4%) of these episodes, whereas 48 (24.6%) were caused by GP. In the group with BSI by GN the most common site of infection was the urinary tract in 68 (46.3%) cases, and in the group with BSI by GP the most common was the primary source in 14 (29.1%) of the cases. The overall mortality of patients with BSI by GN was 19.7% (29 cases) and by BSI in patients with GP was 35.4% (17 cases) (p = 0.03). In multiple logistic regression analysis, the variables associated independently with death in patients with BSI by GN were those who developed respiratory failure requiring mechanical ventilation OR 13,2 IC95=3,07-57,19 (p=0,001), beyond those which had number equal to or greater than two co-morbidities OR 12,4 IC95=1,90-80,35 (p=0,008). In the population with BSI by GP only the respiratory failure requiring mechanical ventilation OR 28,3 IC95=2,53-317,1 (p=0,007) was independently associated with death. Conclusions: Patients with BSI by GN showed the urinary source as the main site of infection, while those with BSI by GP, had the primary source. The presence of more than two co-morbidities was a risk factor for death in patients with BSI by GN. And respiratory failure was a risk factor for death in patients with BSI by GN and GP.